Characterization of Vertical Response of Asphalt Trackbed Concrete in Railway Substructure to External Loads - Bekhzad Yusupov; Yanjun Qiu; Galibjon Sharipov; Chaoyang Wu (Advances in Materials Science and Engineering)
Optimizing the dynamic responses of a slab track system is a key aspect to improve the quality of a railway track structure. In this paper, numerical modelling and simulation of vertical dynamics of the railway track structure engaging the asphalt concrete in substructures were carried out. Thus, a 3D finite element (FE) model was developed. The developed model was validated by comparing its outputs, that is, acceleration with the measured ones from realistic experimental data. The good agreement between the simulated and measured data which resulted from the validation confirmed that the proposed model has a capability of simulating the complex dynamic performances of the train-track-ground system under different loading conditions. Analyses of the determined results from the simulation model performances revealed that three specific factors, which were the speed of the train, the temperature, and thickness of the asphalt concrete trackbed, mainly influenced the dynamic behavior of the railway structure. Thereby, those factors were taken into consideration while evaluating the dynamic responses and designing the asphalt concrete trackbed in railway substructures.